Word Of Mouth Marketing Communication Strategy Japan Tourism Dira Park Balung Jember - Yusnia Nur Zannah Habibi; Mukhamad Zulianto (PT. Faaslib Serambi Media, 2024)
This study aims to describe the word-of-mouth marketing communication strategy of the Japanese tourism company Dira Park Balung Jember Regency. This research is a type of qualitative descriptive research. The methods used are interviews, observation, and documentation. The results showed that the word-of-mouth marketing communication strategy implemented by Japanese tourism Dira Park Balung Jember Regency includes five indicators: talkers, topics, tools, taking parts, and tracking. Speakers (talkers) in marketing communications on this tour are divided into two, namely talkers or intermediaries of predetermined speakers (employees and tour managers) and voluntary speaker intermediaries (visitors, journalists, bloggers, and TV stations). The use of media (tools) includes online media consisting of Facebook, Instagram, WhatsApp, web, YouTube, TV stations, and offline media used through Word of mouth and banner installation. Participation/service (taking Part) carried out by the tour manager is by responding to questions or feedback politely & politely. Second, provide the best service. Third, internal efforts should be made by fostering cohesiveness and brotherhood between employees and maintaining visitors' trust. Fourth, make external efforts by promoting through various aspects. Supervision/control (tracking) is carried out through direct supervision and online supervision by providing criticism and suggestions through the WhatsApp number provided by the tourist.